Evaluation of the segmentation performance of air hydrates from microphotographs of ice thick sections of the EDML ice core - Painer, Florian; Weikusat, Ilka; Kipfstuhl, Sepp (PANGAEA, 2025)
In the deeper part of polar ice sheets, air hydrates are the primary air inclusions. They trap most of the ancient air molecules used for paleoclimatic reconstructions in their crystal structure. Furthermore, their number and size was found to correlate with past climate. Microphotographs of ice thick sections of the EPICA Dronning Maud Land (EDML) ice core were obtained in the years 2002 - 2006 during the Antarctic field season, shortly after the sample was drilled, using an optical microscope (Kipfstuhl et al., 2006; Kipfstuhl, 2007). This dataset presents the segmentation performance of air hydrates from microphotographs of ice thick sections of the EDML ice core. For that, each air hydrate included in eight hand-labeled ground truth (GT) images was automatically compared with the corresponding air hydrate obtained via image segmentation. Furthermore, each hand-labeled air hydrate was differentiated into five visual categories: Above focus (AF), In focus, Below focus (BF), Far out of focus (FOF) and air hydrates that can hardly be distinguished from other image artifacts (X). The images were analyzed by Florian Painer at the Alfred Wegener Institute, Bremerhaven and the analysis routines were implemented in Python using open-source libraries. The aim was to develop a semi-automated analysis routine and to provide a high-resolution record of air hydrate properties of the EDML ice core.
Keywords: air hydrates; EDML; Ice core